Operational Risk Analysis Using an Enterprise Risk Management (ERM) Approach in Startup Companies - Bratandari, RR. Adristi; Waluyowati, Nur Prima (Jurnal Management Risiko dan Keuangan, 2025)
This research discusses the efforts made by startup companies to minimize failures by identifying and analyzing operational risks that might occur in their business processes. The research object is FitAcademy.id by Fitinline.com, a startup company located in Yogyakarta City. The company uses a microlearning-based learning platform. However, various discrepancies in its operations have made the company not run well. This research aims to determine and explain the sources of such operational risk, particularly the biggest obstacles or challenges for the startup company, so that in the future the business owner can make better decisions and control risks. Using the Enterprise Risk Management (ERM) approach, this research found nine incidents of operational risk. Based on the results of the risk assessment, the biggest risk is delays in microlearning video making caused by the external factor, i.e., the client. The results of the analysis on the risk matrix show three levels: high, moderate, and low. The recommended efforts focus on high-level operational risks, namely obstacles in the creation of microlearning products or videos caused by the external factors, and moderate-level operational risks such as delays in work completion, application running errors during explanations to clients, and obstacles in the microlearning video production process caused by internal factors, i.e., talent or facilities, since it greatly influences the performance of all divisions and the company's efficiency in gaining profits.